Renewable Energy Consumption and Economic Growth - Fuinhas, José Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint explores the complex relationship between renewable energy consumption and economic growth. The reprint contains 14 papers covering a wide range of topics related to energy use efficiency in various countries and economic sectors. The articles include studies on adopting renewable energy sources, the impact of battery electric vehicles on greenhouse gas emissions in the European Union, the influence of philanthropy on eco-efficiency, and the impact of energy efficiency regulations on energy poverty. This reprint also includes studies on the race to zero emissions in MINT economies, the competitiveness of the cultural industry and its impact on Chinese economic growth, and the impact of education levels on the energy–growth–environment nexus. This reprint serves as a call to action for all stakeholders to contribute to the global energy transition by identifying and analyzing the effects of renewable energy consumption on economic growth. It inspires policymakers, researchers, and practitioners to embrace sustainable energy practices and support the development of measures that foster green growth. Therefore, this reprint provides important insights into energy use efficiency theories, methods, and diverse applications, making it a valuable resource for anyone interested in the future of energy and its impact on the global economy.